Erratum: Strong circular dichroism for the HE11 mode in twisted single-ring hollow-core photonic crystal fiber (Optica (2018) 5 (1315-1321) DOI: 10.1364/OPTICA.5.001315) - Roth, P.; Chen, Y.; Gunendi, M. C.; Beravat, R.; Edavalath, N. N.; Frosz, M. H.; Ahmed, G.; Wong, G. K.L.; Russell, P. S.J. (Optica, 2022)
Recent work has revealed that the dispersion relation, given inOptica 5, 1315 (2018), for helicalBloch modes in a ring of capillaries surrounding a central hollowcore, is incorrect.Herewe correct this error and provide a revised version of Fig. 2. The overall conclusions of the original paper are unaffected.
CRIS-Team Scopus Importer:2024-12-16